Can gamification improve the virtual reality tourism experience? Analyzing the mediating role of tourism fatigue. (June 2023) - Wei, Zhenda; Zhang, Jingru; Huang, Xiaoting; Qiu, Hanqin
Abstract: Although virtual reality (VR) technology has been increasingly applied in the tourism industry, improving the VR experience of tourists remains a challenge. Based on two studies, this paper examines how gamification can improve the VR tourism experience through reducing tourism fatigue. Study 1 explores the relationship between gamification, tourism fatigue, and tourist satisfaction. The results show that tourists are more satisfied with a gamified, rather than non-gamified, VR tourism experience, and that motivational fatigue plays a mediating role between gamification and tourism satisfaction. Study 2 provides further evidence that four elements in gamification (challenge, feedback, reward, and leaderboard) can alleviate motivational fatigue and improve tourist satisfaction, with feedback playing the biggest role. The findings have valuable practical implications for VR experience providers, for destination practitioners in VR experience enhancement, and for the application of gamification to the VR tourism experience.